Evaluation of Differentiated Learning for Social Studies in theIndependent Curriculum at Semarang Middle Schools - Sritanti, Alvina Ajeng; Juhadi, Juhadi; Handoyo, Eko (Universitas Negeri Semarang, 2024)
Differentiated learning is a fundamental aspect of the Independent Curriculum, officially adopted as Indonesia’s national curriculum in the 2024/2025 academic year. Although the curriculum promotes adaptive and inclusive learning tailored to individual student needs, its implementation in Social Studies (IPS) instruction in middle schools in Semarang City encounters significant challenges. This study evaluates the application of differentiated learning strategies, focusing on planning, implementation, and evaluation stages while identifying obstacles faced by teachers. A mixed-methods approach with an embedded concurrent design was employed, combining quantitative data from ANOVA and Pearson correlation tests with qualitative insights from interviews, classroom observations, and document analysis. Data were collected from four representative schools, with Sekolah Mandiri Berbagi emerging as a model for effective implementation through innovative and adaptive instructional strategies. The findings indicate that schools with comprehensive planning and responsive implementation achieve better learning outcomes. However, challenges such as insufficient teacher training, limited resources, and time constraints hinder the overall effectiveness of differentiated learning. These results underscore the need for strengthening teacher competencies, improving educational infrastructure, and adopting more adaptive teaching approaches. This study offers actionable insights to enhance differentiated instruction under the Independent Curriculum, contributing to educational reform in Indonesia.